Silicon-carbon negative electrode material, preparation method and application thereof

By growing directional graphene sheets in silicon-carbon composite materials and multi-stage carbonization treatment, the structural fracture and interface instability caused by volume expansion of silicon-carbon materials during charging and discharge are solved, and a silicon-carbon negative electrode material with high rate performance and long cycle life is achieved.

CN120221632APending Publication Date: 2025-06-27SHENGHONG KINETIC ENERGY TECH (TAIZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510394024.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-carbon composite materials during charging and discharging leads to structural rupture, interface instability and low-rate performance, making it difficult to meet the needs of fast charging.

Method used

By growing the graphene sheets arranged in a directionally arranged on the surface of the silicon core, a continuous conductive network from the silicon core to the carbon shell is formed, the interface impedance is reduced, and a dense carbon shell and appropriate void structure is formed through multi-stage carbonization treatment, enhancing the mechanical strength of the material and the lithium ion diffusion ability.

Benefits of technology

It significantly improves the cycle stability, rate performance and volume energy density of the material, achieves high specific capacity and long cycle life, and is suitable for electric vehicles and energy storage systems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicon-carbon negative electrode material, a preparation method and application thereof. The silicon-carbon negative electrode material comprises a silicon core; a carbon shell wrapping the silicon core; one end of each graphene sheet is in contact with the silicon core, the other end of each graphene sheet extends to be in contact with the carbon shell, and a gap is formed between every two adjacent graphene sheets. According to the structure, through the synergistic effect of directional arrangement of the graphene sheets and dense coating of the carbon shell, the interface contact resistance is remarkably reduced, the volume expansion stress of the silicon core is relieved, and the conductivity, the mechanical stability and the tap density of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly to a silicon-carbon composite anode material and a preparation method thereof, as well as a negative electrode sheet, a lithium-ion battery containing the material, and their applications in electrical devices. Background Art

[0002] With the rapid growth of the demand for high-energy-density batteries in electric vehicles, portable electronic devices, and energy storage systems, silicon is regarded as an ideal material to replace traditional graphite anodes due to its ultra-high theoretical specific capacity and abundant reserves. However, silicon undergoes severe volume expansion during charge and discharge processes, leading to particle fragmentation, electrode structure collapse, and repeated growth of an unstable solid electrolyte interface (SEI) film, which severely restricts its cycle stability.

[0003] To alleviate the above problems, the structural design of silicon-carbon composite materials is mainly adopted in the prior art, especially the yolk-shell structured silicon / carbon (YS-Si / C) anode material, which buffers volume expansion by leaving voids between the silicon core and the carbon shell. Typical preparation methods include hydrofluoric acid etching method, metal-organic framework template method, and polymer coating-carbonization method: The hydrofluoric acid etching method forms voids by etching the intermediate silica layer, but hydrofluoric acid has strong corrosiveness and high toxicity, resulting in high process hazard and soaring environmental protection costs; The metal-organic framework template method has expensive raw material costs and complex processes, making it difficult to scale up production.

[0004] Although the yolk-shell structure improves the cycle life of silicon anodes to a certain extent, it still has key defects. The point-to-point contact between the encapsulated silicon core and the carbon shell limits the lithium-ion diffusion kinetics of the material, resulting in lower rate performance and higher polarization, making the YS-Si / C anode material unable to meet the current demand for fast charging of power batteries. In addition, during the preparation of commercial electrodes, after coating and drying, rolling is used to improve the bonding strength between the active material and the electrode current collector, thereby preventing delamination caused by electrolyte immersion. Rolling can also compact the porous electrode, reduce the inter-particle contact resistance, and increase the volumetric energy density of the battery. Therefore, the anode material must have sufficient compressive strength to prevent structural damage during the rolling process. However, YS-Si / C materials usually exhibit poor compressive strength, resulting in the collapse of the particle structure during the rolling process. In addition, YS-Si / C materials face new challenges, such as low tap density, so the volumetric energy density is insufficient, which severely hinders their application in actual LIBs. Therefore, there is an urgent need to develop a simple synthesis method to produce YS-Si / C anode materials with high rate performance, mechanical strength, and volumetric energy density. Summary of the Invention

[0005] To overcome the defects in the prior art, the first object of the present invention is to provide a silicon-carbon anode material; the second object of the present invention is to provide a preparation method of the silicon-carbon anode material; the third object of the present invention is to provide a negative electrode sheet; the fourth object of the present invention is to provide a lithium-ion battery; the fifth object of the present invention is to provide an electrical device.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In the first aspect, a silicon-carbon anode material includes:

[0008] A silicon core;

[0009] A carbon shell wrapping the silicon core;

[0010] A plurality of graphene sheets arranged in a direction, one end of the graphene sheet is in contact with the silicon core, the other end extends to contact with the carbon shell, and a gap is formed between adjacent graphene sheets.

[0011] One end of the graphene sheet arranged in a direction is in contact with the silicon core, and the other end extends to contact with the carbon shell, forming a continuous conductive path from the silicon core to the carbon shell. The high conductivity of the graphene sheet directly bridges the silicon active center and the conductive network of the carbon shell, significantly reducing the interfacial impedance between the silicon core and the carbon shell, thereby improving the electron conduction efficiency. At the same time, the gap between adjacent graphene sheets can accommodate the volume expansion of the silicon core, avoid the rupture of the carbon shell, and maintain the integrity of the electrode structure.

[0012] The continuous coating of the carbon shell and the directional arrangement of the graphene sheets work together to reduce the proportion of the inactive area and optimize the internal space utilization rate of the material. The graphene sheet itself provides additional lithium storage capacity through interlayer lithium insertion. Combining with the high specific capacity characteristics of the silicon core, it overcomes the volume energy density loss caused by excessive voids in the traditional yolk-shell structure.

[0013] Preferably, the particle size of the silicon core is 80-100 nm.

[0014] The volume expansion stress generated by the nano-scale silicon core with a size of 80-100 nm during charge and discharge can be dispersed by the graphene sheets arranged in a direction and the carbon shell in a coordinated manner, avoiding the particle rupture caused by the stress concentration of micron-scale silicon. At the same time, it overcomes the serious agglomeration problem caused by the too high surface energy of smaller nano-silicon, ensuring the uniformity and structural stability of the electrode slurry. The specific surface area of the silicon core in this size range is significantly lower than that of smaller nano-silicon, reducing the direct contact area with the electrolyte, inhibiting side reactions and the uncontrollable growth of the SEI film, and improving the first Coulomb efficiency; at the same time, its specific surface area is still higher than that of micron-scale silicon, retaining the fast lithium ion diffusion characteristics of nano-materials.

[0015] Preferably, the thickness of the carbon shell is 10 - 80 nm. More preferably, the thickness of the carbon shell is 20 - 50 nm. Even more preferably, the thickness of the carbon shell is 34 nm. The thickness range of the carbon shell in the present invention can achieve a synergistic optimization among mechanical strength, electrical conductivity, and volumetric energy density. When the thickness of the carbon shell < 10 nm, the constraint on the volume expansion of the silicon core is insufficient; when the thickness of the carbon shell > 80 nm, the energy density loss will be caused by the excessive proportion of inactive materials. When the thickness of the carbon shell is in the range of 10 - 80 nm, it can effectively disperse the stress generated by the expansion of the silicon core, avoid structural rupture, and build an efficient electron transport network through a dense and continuous carbon layer to reduce the interfacial impedance.

[0016] Preferably, the included angle between the directionally arranged graphene sheets and the normal direction of the silicon core surface is 0° - 30°. More preferably, the included angle between the graphene sheets and the normal direction of the silicon core surface is 0°, that is, the graphene sheets are perpendicular to the silicon core surface. The vertically arranged graphene sheets form the shortest conduction path along the axial direction of the silicon core, bridging the silicon core and the carbon shell to maximize the reduction of the interfacial contact resistance. At the same time, their orientation parallel to the volume expansion direction directly absorbs the radial stress of the silicon core through interlayer slip and elastic deformation, avoiding the rupture of the carbon shell; in addition, the parallel voids generated by the vertical arrangement form a directional lithium-ion diffusion channel, significantly reducing the tortuosity of the ion migration path. If the included angle exceeds 30°, the orientation disorder of the void channels will increase the ion diffusion impedance. By limiting the included angle within 0° - 30°, the axial conductivity, stress buffering, and ion diffusion efficiency of the graphene sheets reach an optimal synergy. Combining the silicon core size (80 - 100 nm) and the carbon shell thickness (10 - 80 nm), the synergistic improvement of high specific capacity, high rate performance, and long cycle life is achieved.

[0017] Preferably, the spacing between adjacent graphene sheets is 0.1 - 0.5 nm. More preferably, the spacing between adjacent graphene sheets is 0.35 nm. Setting the spacing between adjacent graphene sheets to 0.1 - 0.5 nm can ensure the rapid diffusion of lithium ions while maintaining a high tap density. Specifically, when the spacing between adjacent graphene sheets < 0.1 nm, it will cause the graphene sheets to stack too densely, hindering the infiltration of the electrolyte and increasing the ion migration resistance. When the spacing between adjacent graphene sheets > 0.5 nm, it will reduce the constraint ability of the graphene sheets on the expansion of the silicon core and introduce too many inactive voids, resulting in a loss of volumetric energy density.

[0018] In a second aspect, a method for preparing a silicon-carbon anode material includes the following steps:

[0019] Growing directionally arranged graphene sheets on the surface of silicon nanoparticles by chemical vapor deposition to form a Si@VGSs composite material;

[0020] Mix the Si@VGSs composite material with polymethyl methacrylate and form a uniform coating layer through melt filling to obtain Si@VGSs@PMMA powder;

[0021] Immerse the Si@VGSs@PMMA powder in a phenolic resin solution and self-assemble to form a surface coating layer through hydrogen bonding to obtain Si@VGSs@PMMA@PFR powder;

[0022] Perform carbonization treatment on the Si@VGSs@PMMA@PFR powder in at least two stages to form a carbon shell and a void structure between the silicon core and the carbon shell.

[0023] By directly growing vertically aligned graphene sheets on the surface of the silicon core, a continuous conductive network from the silicon core to the carbon shell is formed, significantly reducing the interfacial contact resistance. At the same time, since the axial arrangement direction of the graphene sheets is consistent with the volume expansion direction of the silicon core, stress directional transfer and buffering are realized, and the rupture of the carbon shell is inhibited. Polymethyl methacrylate melts and fills the gaps between the graphene sheets to form a uniform pre-coating layer, providing a structural template for the subsequent dense growth of the carbon shell. The phenolic resin is self-assembled and coated through hydrogen bonding to precisely control the thickness of the carbon shell and avoid local stress concentration caused by uneven coating layers. Staged heating carbonization realizes the gradual decomposition of the polymer and the orderly reconstruction of the carbon layer, avoiding the problem of pore out-of-control in single-stage carbonization. The micropores generated by the decomposition of polymethyl methacrylate and the gaps between the graphene sheets cooperate to form controllable voids, precisely adapting to the expansion space of the silicon core while maintaining a high tapped density.

[0024] Preferably, the chemical vapor deposition is thermal chemical vapor deposition, using a mixed gas of hydrogen and methane, with a hydrogen flow rate of 90 - 110 mL / min and a methane flow rate of 10 - 30 mL / min. Further preferably, the hydrogen flow rate is 100 mL / min and the methane flow rate is 20 mL / min.

[0025] The setting of this gas ratio and flow rate range optimizes the growth quality and material properties of graphene sheets (VGSs) through synergistic effects. Hydrogen is cracked in a high-temperature environment to produce active hydrogen atoms, whose core functions include reducing the oxide layer on the surface of the silicon core, activating the silicon lattice to provide graphene nucleation sites, and inhibiting disordered carbon deposition. When the hydrogen flow rate is lower than 90 mL / min, the reduction of the silicon surface is insufficient, resulting in an increase in the defect density of graphene; when the flow rate is higher than 110 mL / min, excessive hydrogen atoms may etch the already formed graphene sheets, damaging the structural integrity. Methane, as a carbon source, is cracked to generate carbon atoms, and its flow rate control directly affects the carbon supply rate and graphene growth kinetics. When the methane flow rate is lower than 10 mL / min, the carbon source is insufficient, leading to a decrease in graphene coverage; when the flow rate is higher than 30 mL / min, the carbon deposition is too fast, easily causing multi-layer stacking or disordered carbon generation.

[0026] Preferably, the mass ratio of the polymethyl methacrylate to the silicon nanoparticles is (0.5 - 1):1. More preferably, the mass ratio of the polymethyl methacrylate to the silicon nanoparticles is 0.6:1. This mass ratio range realizes the full filling and structure optimization of the surface of the silicon core and the gaps between the graphene sheets by regulating the thickness and uniformity of the polymer coating layer. When the amount of polymethyl methacrylate used is too small (mass ratio < 0.5:1), the polymer cannot completely cover the surfaces of the silicon core and the graphene sheets, resulting in uneven self-assembly coating of phenolic resin in the subsequent process, and local defects in the carbon shell after carbonization. When the amount of polymethyl methacrylate used is too large (mass ratio > 1:1), the too-thick polymer layer is prone to form large-size pores or structural collapse due to the concentrated release of pyrolysis gas during the carbonization process, reducing the tapped density. When the mass ratio is further preferably 0.6:1, the polymethyl methacrylate can uniformly penetrate into the gaps between the graphene sheets and completely coat the surface of the silicon core after melting, providing a flat substrate for the self-assembly of phenolic resin. At the same time, the thickness of the carbon shell and the size of the internal voids are precisely controlled through subsequent multi-stage carbonization. The carbon shell formed at this ratio has both compactness and appropriate elasticity, which can not only effectively restrain the volume expansion of the silicon core but also avoid the increase in lithium-ion diffusion resistance caused by too thick carbon layer, thus realizing the synergistic optimization of high tapped density and high rate performance.

[0027] Preferably, the carbonization treatment in at least two stages includes:

[0028] The first stage is treated at 330 - 350 °C for 1.5 - 2.5 hours, and the heating rate is 1 - 3 °C / min;

[0029] The second stage is treated at 440 - 460 °C for 2.5 - 3.5 hours, and the heating rate is 4 - 6 °C / min;

[0030] The third stage is carbonized at 880 - 920 °C for 2.5 - 3.5 hours, and the heating rate is 8 - 12 °C / min.

[0031] By setting three carbonization stages, the thermal decomposition process is precisely regulated to achieve the densification of the carbon shell and the optimization of the pore structure. In the first stage, it is treated at 330 - 350 °C for 1.5 - 2.5 hours with a heating rate of 1 - 3 °C / min, enabling the slow decomposition of polymethyl methacrylate (PMMA) to generate uniform micropores, avoiding the structural collapse caused by the concentrated release of gas, and simultaneously retaining the initial morphology of the gaps between graphene sheets. In the second stage, it is treated at 440 - 460 °C for 2.5 - 3.5 hours with a heating rate of 4 - 6 °C / min, promoting the pre-carbonization of phenolic resin (PF) to form a cross-linked carbon skeleton, stabilizing the pore structure and enhancing the mechanical strength of the carbon shell. In the third stage, it is carbonized at 880 - 920 °C for 2.5 - 3.5 hours with a heating rate of 8 - 12 °C / min, achieving the high-temperature graphitization of the carbon shell, improving the conductivity and eliminating residual organic substances, and finally forming a dense and continuous carbon coating layer with a thickness of 10 - 80 nm and the gap size between it and the silicon core controlled within 10 - 50 nm. The multi-stage carbonization process ensures that the carbon shell has both high crystallinity and a controllable pore distribution through stepwise heating and rate matching, effectively restraining the volume expansion of the silicon core and maintaining the stability of the lithium-ion diffusion channel.

[0032] In the third aspect, a negative electrode sheet includes the above-mentioned silicon-carbon negative electrode material, a conductive agent, and a binder.

[0033] In the fourth aspect, a lithium-ion battery includes the above-mentioned negative electrode sheet.

[0034] In the fifth aspect, an electrical device includes the above-mentioned lithium-ion battery.

[0035] Due to the application of the above technical solutions, the present invention has the following advantages compared with the prior art:

[0036] 1. The graphene sheets arranged in an oriented manner penetrate the silicon core and the carbon shell, forming a three-dimensional continuous conductive network, significantly reducing the interfacial contact resistance. At the same time, their orientation parallel to the volume expansion direction absorbs the radial stress of the silicon core through interlayer slip and elastic deformation, inhibiting the rupture of the carbon shell and enhancing the cycle stability (the capacity retention rate after 1000 cycles > 83%). The gaps between the graphene sheets provide a directional diffusion channel for lithium ions, shortening the migration path and achieving high-rate performance.

[0037] 2. The matching design of the silicon core particle size (80 - 100 nm) and the carbon shell thickness (10 - 80 nm) reduces the proportion of inactive materials while suppressing volume expansion. Combining with the interlayer lithium storage capacity of the graphene sheets, the tap density and the volume energy density of the material are both higher than those of traditional silicon-carbon materials.

[0038] 3. Achieve full - process hydrofluoric acid (HF) - free etching through chemical vapor deposition, polymer self - assembly, and multi - stage carbonization, avoiding the use of high - risk chemicals; PMMA melt filling and hydrogen - bond self - assembly of PF resin ensure the uniformity of the coating layer, and multi - stage carbonization precisely controls the denseness and void structure of the carbon shell, taking into account both process safety and material consistency.

[0039] 4. The negative electrode sheet containing this silicon - carbon material still maintains excellent interfacial stability and adaptability to the rolling process under high loading. The assembled lithium - ion battery has high energy density, long cycle life, and low polarization characteristics, and is applicable to electric devices such as electric vehicles and energy storage systems.

[0040] To make the above - mentioned and other purposes, features, and advantages of the present invention more obvious and understandable, the following preferred embodiments are specifically given and described in detail as follows. Detailed implementation manners

[0041] The technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the protection scope of the present invention.

[0042] Example 1:

[0043] This example discloses a silicon - carbon negative electrode material, including:

[0044] A silicon core;

[0045] A carbon shell wrapping the silicon core;

[0046] Multiple graphene sheets arranged in an oriented manner, one end of the graphene sheet contacts the silicon core, the other end extends to contact the carbon shell, and voids are formed between adjacent graphene sheets.

[0047] The particle size of the silicon core is 80 - 100 nm. The thickness of the carbon shell is 10 - 80 nm. The included angle between the oriented graphene sheets and the normal direction of the silicon core surface is 0° - 30°. The distance between adjacent graphene sheets is 0.1 - 0.5 nm.

[0048] Example 2:

[0049] This example discloses a preparation method of the silicon - carbon negative electrode material in Example 1, including the following steps:

[0050] Step 1: Pretreatment of the silicon core

[0051] Select silicon nanoparticles with a particle size of 80 nm as raw materials, remove the surface oxide layer by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dry under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0052] Step 2: Growth of vertically aligned graphene sheets (VGSs)

[0053] Evenly spread 1 g of the pretreated silicon nanoparticles on a quartz boat and place it in the reaction chamber of a tube furnace.

[0054] Heat to 1100 °C at a rate of 10 °C / min under an argon atmosphere.

[0055] Switch to a mixed gas of hydrogen (100 mL / min) and methane (20 mL / min), and maintain for 1 hour. Vertically aligned graphene sheets grow on the silicon surface to form a Si@VGSs composite material.

[0056] Naturally cool to room temperature, and collect the product Si@VGSs composite material (vertically grown graphene sheets on the silicon core) under argon protection.

[0057] Step 3: PMMA coating

[0058] Mix 1 g of the Si@VGSs composite material with poly(methyl methacrylate) (PMMA, 0.6 g) at a mass ratio of 1:0.6; add anhydrous ethanol as a dispersion medium and ball-mill for 2 hours at 500 rpm to form a homogeneous mixture.

[0059] Transfer the mixture to a vacuum oven and heat at 150 °C for 12 hours to allow PMMA to melt and fill the gaps between the graphene sheets.

[0060] After cooling to room temperature, grind and pass through a 500-mesh sieve to obtain Si@VGSs@PMMA powder.

[0061] Step 4: Self-assembly coating of PF resin

[0062] Dissolve phenolic resin (PF, 0.6 g) in ethanol (10 mL) to prepare a 6 wt% solution.

[0063] Disperse 1.2 g of Si@VGSs@PMMA powder in a 6 wt% phenolic resin (PF) ethanol solution and stir at room temperature for 5 minutes.

[0064] Let the obtained suspension stand for 30 minutes to allow PF to self-assemble into a uniform coating layer on the powder surface through hydrogen bonding. Centrifuge to collect the precipitate, and then place the precipitate in a forced-air drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin.

[0065] The obtained lumps were ground and passed through a 20-μm sieve to obtain Si@VGSs@PMMA@PFR powder.

[0066] Step Five: Multi-stage carbonization

[0067] First stage: The Si@VGSs@PMMA@PFR powder was placed in a tube furnace. Under argon protection, it was heated to 340 °C at a rate of 2 °C / min and held for 2 hours to allow PMMA to slowly decompose to form micropores.

[0068] Second stage: It was heated to 450 °C at a rate of 5 °C / min and held for 3 hours to promote the pre-carbonization of PF to form a cross-linked carbon skeleton.

[0069] Third stage: It was heated to 900 °C at a rate of 10 °C / min and held for 3 hours to achieve the complete carbonization of PF into a dense carbon shell, and finally obtain the VGSs-YS-Si / C composite material.

[0070] This example also discloses a preparation method of a negative electrode sheet having the above VGSs-YS-Si / C composite material, including the following steps:

[0071] The VGSs-YS-Si / C composite material, a conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) were mixed in deionized water at a weight ratio of 80:10:4:3:3 to form an electrode slurry.

[0072] The electrode slurry was coated on a copper foil current collector with a blade and vacuum dried at 80 °C for 24 hours, and then cut into circular working electrodes with a diameter of 12 mm.

[0073] Example 3:

[0074] This example also discloses a preparation method of a negative electrode material, including the following steps:

[0075] Step One: Silicon nanoparticles with a particle size of 80 nm were selected as raw materials. The surface oxide layer was removed by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dried under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0076] Step Two: The pretreated silicon nanoparticles were evenly spread on a quartz boat and placed in the reaction chamber of a tube furnace.

[0077] Under an argon atmosphere, it was heated to 1000 °C at a rate of 10 °C / min.

[0078] The gas was switched to a mixed gas of argon (100 mL / min) and methane (20 mL / min) and maintained for 1 hour to obtain the Si@C composite material.

[0079] Naturally cool to room temperature, and collect the product Si@C composite material under argon protection.

[0080] Step 3: Mix the Si@C composite material (1 g) and polymethyl methacrylate (PMMA, 0.6 g) at a mass ratio of 1:0.6; add absolute ethanol as the dispersion medium, and ball mill for 2 hours at 500 rpm to form a homogeneous mixture;

[0081] Transfer the mixture to a vacuum oven and heat at 150 °C for 12 hours;

[0082] After cooling to room temperature, grind and pass through a 500-mesh sieve to obtain Si@C@PMMA powder.

[0083] Step 4: Dissolve phenolic resin (PF, 0.6 g) in ethanol (10 mL) to prepare a 6 wt% solution;

[0084] Disperse 1.2 g of Si@C@PMMA powder in a 6 wt% phenolic resin (PF) ethanol solution and stir at room temperature for 5 minutes;

[0085] Let the obtained suspension stand for 30 minutes, centrifuge to collect the precipitate, then place the precipitate in a blast drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin;

[0086] Grind the obtained block and pass through a 20-μm sieve to obtain Si@C@PMMA@PFR powder.

[0087] Step 5:

[0088] The first stage: Place the Si@C@PMMA@PFR powder in a tube furnace, heat it to 340 °C at a rate of 2 °C / min under argon protection, and hold for 2 hours;

[0089] The second stage: Heat it to 450 °C at a rate of 5 °C / min and hold for 3 hours;

[0090] The third stage: Heat it to 900 °C at a rate of 10 °C / min and hold for 3 hours to finally obtain the C-YS-Si / C composite material.

[0091] This example also discloses a method for preparing a negative electrode plate with the above C-YS-Si / C composite material, including the following steps:

[0092] Mix the C-YS-Si / C composite material, conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) in deionized water at a weight ratio of 80:10:4:3:3 to form an electrode slurry;

[0093] Coat the electrode paste on the copper foil current collector with a blade, dry it in vacuum at 80 °C for 24 hours, and then cut it into circular working electrodes with a diameter of 12 mm.

[0094] Example 4:

[0095] This example also discloses a preparation method of a silicon-carbon anode material, which is characterized by including the following steps:

[0096] Step 1: Select silicon nanoparticles with a particle size of 80 nm as raw materials, remove the surface oxide layer by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dry them under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0097] Step 2: Uniformly spread the pretreated silicon nanoparticles on a quartz boat and place them in the reaction chamber of a tube furnace; heat to 1100 °C at a rate of 10 °C / min under an argon atmosphere.

[0098] Step 3: Mix Si (1 g) and polymethyl methacrylate (PMMA, 0.6 g) according to a mass ratio of 1:0.6; add anhydrous ethanol as a dispersion medium and ball mill for 2 hours at 500 rpm to form a uniform mixture;

[0099] Transfer the mixture to a vacuum oven and heat at 150 °C for 12 hours;

[0100] After cooling to room temperature, grind and pass through a 500-mesh sieve to obtain Si@PMMA powder.

[0101] Step 4: Dissolve phenolic resin (PF, 0.6 g) in ethanol (10 mL) to prepare a 6 wt% solution;

[0102] Disperse 1.2 g of Si@PMMA powder in a 6 wt% phenolic resin (PF) ethanol solution and stir at room temperature for 5 minutes;

[0103] Let the obtained suspension stand for 30 minutes, centrifuge to collect the precipitate, and then place the precipitate in a blast drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin;

[0104] Grind the obtained block and pass through a 20-μm sieve to obtain Si@PMMA@PFR powder.

[0105] Step 5:

[0106] The first stage: Place the Si@PMMA@PFR powder in a tube furnace and heat to 340 °C at a rate of 2 °C / min under argon protection, and hold for 2 hours;

[0107] The second stage: Heat to 450 °C at a rate of 5 °C / min and hold for 3 hours;

[0108] The third stage: heat it up to 900 °C at a rate of 10 °C / min and hold for 3 hours to finally obtain the YS-Si / C composite material.

[0109] This example also discloses a preparation method of a negative electrode sheet having the above YS-Si / C composite material, including the following steps:

[0110] Mix the YS-Si / C composite material, a conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) in deionized water at a weight ratio of 80:10:4:3:3 to form an electrode slurry;

[0111] Coat the electrode slurry on a copper foil current collector with a blade, dry it in vacuum at 80 °C for 24 hours, and then cut it into circular working electrodes with a diameter of 12 mm.

[0112] Example 5:

[0113] This example also discloses a preparation method of a silicon-carbon negative electrode material, including the following steps:

[0114] Step 1:

[0115] Select silicon nanoparticles with a particle size of 80 nm as raw materials, remove the surface oxide layer by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dry it under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0116] Step 2:

[0117] Evenly spread 1 g of the pretreated silicon nanoparticles on a quartz boat and place it in the reaction chamber of a tube furnace;

[0118] Heat it up to 1100 °C at a rate of 10 °C / min under an argon atmosphere;

[0119] Switch to a mixed gas of hydrogen (100 mL / min) and methane (20 mL / min), maintain for 1 hour to form the Si@VGSs composite material;

[0120] Cool it naturally to room temperature and collect the product Si@VGSs composite material under argon protection.

[0121] Step 3:

[0122] Mix the Si@VGSs composite material (1 g) and polymethyl methacrylate (PMMA, 0.6 g) at a mass ratio of 1:0.6; add absolute ethanol as a dispersion medium and ball mill for 2 hours at 500 rpm to form a uniform mixture;

[0123] Transfer the mixture to a vacuum oven and heat it at 150 °C for 12 hours;

[0124] After cooling to room temperature, it was ground and passed through a 500-mesh sieve to obtain Si@VGSs@PMMA powder.

[0125] Step Four:

[0126] Phenolic resin (PF, 0.6 g) was dissolved in ethanol (10 mL) to prepare a 6 wt% solution.

[0127] 1.2 g of Si@VGSs@PMMA powder was dispersed in a 6 wt% phenolic resin (PF) ethanol solution and stirred at room temperature for 5 minutes.

[0128] The obtained suspension was allowed to stand for 30 minutes, and the precipitate was collected by centrifugation. Then the precipitate was placed in a forced-air drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin.

[0129] The obtained block was ground and passed through a 20-μm sieve to obtain Si@VGSs@PMMA@PFR powder.

[0130] Step Five:

[0131] The Si@VGSs@PMMA@PFR powder was placed in a tube furnace and heated to 900 °C at a rate of 10 °C / min under argon protection, and held for 3 hours to finally obtain VGSs-YS-Si / C composite material.

[0132] This example also discloses a method for preparing a negative electrode sheet having the above VGSs-YS-Si / C composite material, including the following steps:

[0133] The VGSs-YS-Si / C composite material, conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) were mixed in deionized water at a weight ratio of 80:10:4:3:3 to form an electrode slurry.

[0134] The electrode slurry was coated on a copper foil current collector with a blade and vacuum dried at 80 °C for 24 hours, and then cut into circular working electrodes with a diameter of 12 mm.

[0135] Example 6:

[0136] This example discloses a method for preparing a negative electrode sheet, including the following steps:

[0137] Step One:

[0138] Silicon nanoparticles with a particle size of 80 nm were selected as raw materials, and the surface oxide layer was removed by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dried under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0139] Step 2:

[0140] Evenly spread 1 g of pre-treated silicon nanoparticles on a quartz boat and place it in the reaction chamber of a tube furnace.

[0141] Under an argon atmosphere, heat it to 1100 °C at a rate of 10 °C / min.

[0142] Switch to a mixed gas of hydrogen (100 mL / min) and methane (20 mL / min), and maintain for 1 hour. Vertically aligned graphene sheets grow on the silicon surface to form a Si@VGSs composite material.

[0143] Naturally cool to room temperature, and collect the product Si@VGSs composite material (vertically growing graphene sheets on the silicon core) under argon protection.

[0144] Step 3:

[0145] Mix 1 g of the Si@VGSs composite material with polymethyl methacrylate (PMMA, 0.6 g) at a mass ratio of 1:0.6; add anhydrous ethanol as a dispersion medium and ball mill for 2 hours at 500 rpm to form a homogeneous mixture.

[0146] Transfer the mixture to a vacuum oven and heat at 150 °C for 12 hours to allow PMMA to melt and fill the gaps between the graphene sheets.

[0147] After cooling to room temperature, grind and pass through a 500-mesh sieve to obtain Si@VGSs@PMMA powder.

[0148] Step 4: Self-assembly coating of PF resin

[0149] Dissolve phenolic resin (PF, 0.6 g) in ethanol (10 mL) to prepare a 6 wt% solution.

[0150] Disperse 1.2 g of Si@VGSs@PMMA powder in a 6 wt% phenolic resin (PF) ethanol solution and stir at room temperature for 5 minutes.

[0151] Let the obtained suspension stand for 30 minutes to allow PF to self-assemble into a uniform coating layer on the powder surface through hydrogen bonding. Centrifuge to collect the precipitate, and then place the precipitate in a blast drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin.

[0152] Grind the obtained block and pass through a 20-μm sieve to obtain Si@VGSs@PMMA@PFR powder.

[0153] Step 5: Multi-stage carbonization

[0154] The first stage: Place the Si@VGS s@PMMA@PFR powder in a tube furnace. Under argon protection, heat it to 340 °C at a rate of 2 °C / min and hold for 2 hours to slowly decompose PMMA to form micropores.

[0155] The second stage: Heat it to 450 °C at a rate of 5 °C / min and hold for 3 hours to promote the pre-carbonization of PF to form a cross-linked carbon skeleton.

[0156] The third stage: Heat it to 900 °C at a rate of 10 °C / min and hold for 3 hours to completely carbonize PF into a dense carbon shell, and finally obtain the VGS s-YS-Si / C composite material.

[0157] Step six:

[0158] Mix the VGS s-YS-Si / C composite material, conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) in deionized water at a weight ratio of 85:7:3:3:2 to form an electrode slurry.

[0159] Use a blade to coat the electrode slurry on a copper foil current collector, dry it in vacuum at 80 °C for 24 hours, and then cut it into circular working electrodes with a diameter of 12 mm.

[0160] Example 7:

[0161] This example discloses a preparation method of a negative electrode material, including the following steps:

[0162] Step one:

[0163] Select silicon nanoparticles with a particle size of 80 nm as raw materials, remove the surface oxide layer by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dry it under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0164] Step two:

[0165] Evenly spread 1 g of pretreated silicon nanoparticles on a quartz boat and place it in the reaction chamber of a tube furnace.

[0166] Under an argon atmosphere, heat it to 1100 °C at a rate of 10 °C / min.

[0167] Switch to a mixed gas of hydrogen (100 mL / min) and methane (20 mL / min), maintain for 1 hour, and grow vertically aligned graphene sheets on the silicon surface to form the Si@VGS s composite material.

[0168] Cool naturally to room temperature and collect the product Si@VGS s composite material under argon protection.

[0169] Step three:

[0170] Mix the Si@VGSs composite material (1 g) and polymethyl methacrylate (PMMA, 1.2 g) in a mass ratio of 1:1.2; add absolute ethanol as the dispersion medium and ball-mill for 2 hours at 500 rpm to form a homogeneous mixture;

[0171] Transfer the mixture to a vacuum oven, heat at 150 °C for 12 hours, cool to room temperature, grind, and then pass through a 500-mesh sieve to obtain Si@VGSs@PMMA powder.

[0172] Step Four:

[0173] Dissolve phenolic resin (PF, 0.6 g) in ethanol (10 mL) to prepare a 6 wt% solution;

[0174] Disperse 1.2 g of Si@VGSs@PMMA powder in a 6 wt% phenolic resin (PF) ethanol solution and stir at room temperature for 5 minutes;

[0175] Let the obtained suspension stand for 30 minutes to allow PF to self-assemble into a uniform coating layer on the powder surface through hydrogen bonding, centrifuge to collect the precipitate, then place the precipitate in a blast drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin;

[0176] Grind the obtained block and pass through a 20-μm sieve to obtain Si@VGSs@PMMA@PFR powder.

[0177] Step Five:

[0178] First stage: Place the Si@VGSs@PMMA@PFR powder in a tube furnace, heat from room temperature to 340 °C at a rate of 2 °C / min under argon protection, and hold for 2 hours;

[0179] Second stage: Heat from 340 °C to 450 °C at a rate of 5 °C / min and hold for 3 hours;

[0180] Third stage: Heat from 450 °C to 900 °C at a rate of 10 °C / min and hold for 3 hours to finally obtain the VGSs-YS-Si / C composite material.

[0181] This example also discloses a method for preparing a negative electrode plate with the above VGSs-YS-Si / C composite material, including the following steps:

[0182] Mix the VGSs-YS-Si / C composite material, conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) in deionized water in a weight ratio of 80:10:4:3:3 to form an electrode slurry;

[0183] The electrode paste was coated on the copper foil current collector with a blade, vacuum dried at 80 °C for 24 hours, and then cut into circular working electrodes with a diameter of 12 mm.

[0184] Example 8:

[0185] This example discloses a preparation method of a negative electrode material, including the following steps:

[0186] Step 1:

[0187] Silicon nanoparticles with a particle size of 80 nm were selected as raw materials, and the surface oxide layer was removed by pickling (a mixed solution of hydrofluoric acid and nitric acid), and then dried under nitrogen protection to obtain silicon nanoparticles with a clean surface.

[0188] Step 2:

[0189] 1 g of the pretreated silicon nanoparticles were evenly spread on a quartz boat and placed in the reaction chamber of a tube furnace;

[0190] Under an argon atmosphere, it was heated to 1100 °C at a rate of 10 °C / min;

[0191] It was switched to a mixed gas of hydrogen (110 mL / min) and methane (10 mL / min) and maintained for 1 hour, and vertically aligned graphene sheets grew on the silicon surface to form a Si@VGSs composite material;

[0192] It was naturally cooled to room temperature, and the product Si@VGSs composite material was collected under argon protection.

[0193] Step 3:

[0194] The Si@VGSs composite material (1 g) and polymethyl methacrylate (PMMA, 0.6 g) were mixed at a mass ratio of 1:0.6; anhydrous ethanol was added as a dispersion medium, and ball milled at 500 rpm for 2 hours to form a uniform mixture;

[0195] The mixture was transferred to a vacuum oven, heated at 150 °C for 12 hours, cooled to room temperature, ground, and sieved through a 500-mesh sieve to obtain Si@VGSs@PMMA powder.

[0196] Step 4:

[0197] Phenolic resin (PF, 0.6 g) was dissolved in ethanol (10 mL) to prepare a 6 wt% solution;

[0198] 1.2 g of Si@VGSs@PMMA powder was dispersed in a 6 wt% phenolic resin (PF) ethanol solution and stirred at room temperature for 5 minutes;

[0199] Let the obtained suspension stand for 30 minutes to allow PF to self-assemble into a uniform coating layer on the powder surface through hydrogen bonding. Centrifuge to collect the precipitate, and then place the precipitate in a forced-air drying oven at 70 °C for 6 hours, and then at 90 °C for 24 hours to cure the resin;

[0200] Grind the obtained block and sieve it through a 20-μm sieve to obtain Si@VGSs@PMMA@PFR powder.

[0201] Step Five:

[0202] First stage: Place the Si@VGSs@PMMA@PFR powder in a tubular furnace and heat it to 340 °C at a rate of 2 °C / min under argon protection, and hold for 2 hours;

[0203] Second stage: Heat it to 450 °C at a rate of 5 °C / min and hold for 3 hours;

[0204] Third stage: Heat it to 900 °C at a rate of 10 °C / min and hold for 3 hours to finally obtain the VGSs-YS-Si / C composite material.

[0205] This example also discloses a method for preparing a negative electrode sheet having the above VGSs-YS-Si / C composite material, including the following steps:

[0206] Mix the VGSs-YS-Si / C composite material, conductive additive (SuperP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR) in deionized water at a weight ratio of 80:10:4:3:3 to form an electrode slurry;

[0207] Use a blade to coat the electrode slurry on a copper foil current collector, vacuum dry at 80 °C for 24 hours, and then cut it into circular working electrodes with a diameter of 12 mm.

[0208] Assemble a full cell with NCM811 as the positive electrode and the negative electrode sheet prepared in Examples 2-8 above, and conduct a cycle performance test. The results are shown in the following table:

[0209] Group Number of cycles Capacity retention rate (%) Coulombic efficiency (%) Example 2 1000 83.1 99.89 Example 3 1000 78.4 99.58 Example 4 1000 75.9 99.42 Example 5 600 70 95.13 Example 6 850 77.1 98.74 Example 7 850 80.3 99.25 Example 8 850 82.9 98.97

[0210] It can be seen from the above test results that:

[0211] Example 2 (VGS s-YS-S i / C) exhibits the most excellent comprehensive performance. After 1000 cycles, its capacity retention rate reaches 83.1%, and the Coulombic efficiency is as high as 99.89%. This advantage is mainly attributed to the three-dimensional continuous conductive network constructed by vertical graphene sheets (VGS s) between the silicon core and the carbon shell, which significantly reduces the interfacial contact resistance. At the same time, the oriented arrangement of VGS s effectively absorbs the radial stress generated by the volume expansion of the silicon core and inhibits the rupture of the carbon shell. In addition, the parallel voids between VGS s form an oriented lithium-ion diffusion channel, shortening the ion migration path, increasing the lithium-ion diffusion coefficient, and thus taking into account both high-rate performance and cycling stability. In contrast, in Example 3 (C-YS-S i / C), due to the absence of VGS s, the conductive network is discontinuous and the stress buffering ability is insufficient, resulting in a decrease in the capacity retention rate to 78.4%, and the Coulombic efficiency needs 14 cycles to stabilize, fully verifying the core role of VGSs.

[0212] The multi-stage carbonization process is crucial for the structural regulation of the material. Example 2 uses three-stage carbonization (340 °C → 450 °C → 900 °C). By stepwise decomposing PMMA and PF resins, the denseness of the carbon shell and the internal void size (30 - 40 nm) are precisely controlled, and the tap density reaches 1.2 g / cm 3 . In contrast, Example 5 uses a single-stage carbonization process of directly heating to 900 °C. The rapid decomposition of PMMA generates large-sized pores, leading to the out-of-control growth of the SEI film caused by electrolyte penetration. After 600 cycles, the capacity retention rate drops sharply to 70%, and the Coulombic efficiency is only 95.13%, indicating that staged temperature control is the key to avoiding structural deterioration. The synergistic coating of PMMA and PF resins further optimizes the material performance. In Example 1, the mass ratio of PMMA to silicon of 0.6:1 achieves the best balance between the void size and the carbon shell thickness (80 nm). In Example 7, when the PMMA ratio is increased to 1.2:1, although the capacity retention rate is slightly increased (80.3%), the tap density is reduced to 0.8 g / cm 3 due to the too thick carbon shell, proving that a compromise needs to be sought between the coating thickness and void regulation.

[0213] The electrode slurry ratio has a significant impact on the interfacial stability. Example 2 uses a ratio of 80% active material, 10% conductive agent, and 10% binder to construct a balanced conductive network and interfacial bonding force. In Example 6, after reducing the conductive agent ratio to 7% and adjusting the binder to 8%, the interfacial resistance increases, resulting in a decrease in the capacity retention rate to 77.1%, indicating that the ratio of the conductive agent to the binder needs to be strictly matched to maintain the integrity of the electrode structure.

[0214] In Example 8 compared with Example 2, since fewer vertical graphene are obtained, the mechanical properties and conductivity of the silicon-carbon negative electrode become worse.

[0215] Comparing the performance of each embodiment comprehensively, Embodiment 2 is significantly superior to other solutions in terms of tap density, compressive strength, and volume energy density.

[0216] In the present invention, specific embodiments are used to elaborate on the principles and implementation manners of the present invention. The descriptions of the above embodiments are only used to help understand the method and its core idea of the present invention; at the same time, for those of ordinary skill in the art, according to the idea of the present invention, there will be changes in the specific implementation manners and application scopes. In summary, the content of this specification should not be construed as a limitation to the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: include: Silicon core; a carbon shell surrounding the silicon core; A plurality of graphene sheets are arranged in a direction, wherein one end of the graphene sheet contacts the silicon core, the other end of the graphene sheet extends to contact the carbon shell, and gaps are formed between adjacent graphene sheets.

2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The particle size of the silicon core is 80-100 nm.

3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The thickness of the carbon shell is 10 to 80 nm.

4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The angle between the directional graphene sheets and the normal direction of the silicon core surface is 0° to 30°.

5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The spacing between adjacent graphene sheets is 0.1 to 0.5 nm.

6. A method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: Directed graphene sheets are grown on the surface of silicon nanoparticles by vapor deposition to form Si@VGS s composite materials; The Si@VGS s composite material is mixed with polymethyl methacrylate, and a uniform coating layer is formed by melt filling to obtain Si@VGS s@PMMA powder; The Si@VGS s@PMMA powder is immersed in a phenolic resin solution to form a surface coating layer through self-assembly through hydrogen bonding to obtain Si@VGS s@PMMA@PFR powder; The Si@VGS s@PMMA@PFR powder is subjected to at least two stages of carbonization treatment to form a carbon shell and a void structure between the silicon core and the carbon shell.

7. The preparation method according to claim 6, characterized in that: The vapor deposition is thermal chemical vapor deposition, using a mixed gas of hydrogen and methane, with a hydrogen flow rate of 90 to 110 mL / min and a methane flow rate of 10 to 30 mL / min.

8. The preparation method according to claim 6, characterized in that: The mass ratio of the polymethyl methacrylate to the silicon nanoparticles is (0.5-1):

1.

9. The preparation method according to claim 6, characterized in that: The at least two-stage carbonization process comprises: The first stage is treated at 330-350℃ for 1.5-2.5 hours, with a heating rate of 1-3℃ / min; The second stage is treated at 440-460°C for 2.5-3.5 hours, with a heating rate of 4-6°C / min; The third stage is carbonization at 880-920°C for 2.5-3.5 hours, with a heating rate of 8-12°C / min.

10. A negative electrode plate, characterized in that: It comprises the silicon-carbon negative electrode material according to any one of claims 1 to 5, a conductive agent and a binder.

11. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 10.

12. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 11.